Connecting Pre-service Teachers and Experienced Educators: Social Media for Lifelong Learning - Kumar, Swapna; Leeman, Jessica (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2013)
Beginning teachers often feel isolated and either lack role models or find it difficult to reach out to more experienced teachers. An educational technology course connected beginning teachers with experienced educators using social media. An analysis of pre-service teachers’ (n=15) reflections indicated that online interactions with experts had provided them with resources, role models, best practice examples, and skills for technology integration and lifelong learning. The results underscore the potential of social media, professional networks, and communities of practice to provide pre-service teachers with real-world experiences and connections with experienced teachers.